The use of a human body model to determine the variation of path losses in the human body channel in wireless capsule endoscopy - Basar, Md R.; Mohd Fareq, Abdul Malek, Dr.; Khairudi M., Juni; Mustafa Iskandar M., Saleh; Mohd Shaharom, Idris; Latifah, Mohamed; Norshafinash, Saudin; Nur Adyani, Mohd Affendi; Abdussalam Salhin Mohamed, Ali (Progress in Electromagnetics Research (PIER), 2013)
Link to publisher's homepage at http://www.jpier.org/PIER/